To the problem of continuity of many-valued mappings - Ostapenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the problem of the upper and lower semicontinuity of the union and intersection for a family of many-valued mappings. We establish new conditions of lower semicontinuity for the intersection of a family of lower semicontinuous mappings.